2015
DOI: 10.3109/09273948.2015.1037845
|View full text |Cite
|
Sign up to set email alerts
|

Brimonidine Induced Anterior Uveitis

Abstract: Ophthalmologists should be aware of this easily reversible uveitis syndrome that is induced by a common glaucoma medication. Familiarity with this entity is essential in making the correct diagnosis and avoiding unnecessary investigations and interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 22 publications
2
18
1
7
Order By: Relevance
“…In the present study, multiple linear regression analysis indicated a negative correlation between anterior flare reduction and combination therapy of K-115 and α2-agonists, which suggests that α2-agonists with or without K-115 possibly increase anterior inflammation in uveitis with OHT. Previous reports have proposed that adrenergic agonists decrease the volume of conjunctival cells and widen the space between cells, allowing greater access of pro-inflammatory agents and continued topical administration of α2-agonists in eyes with allergic reactions may predispose to the development of uveitis [ 24 ]. Histological findings of conjunctivitis and anterior uveitis induced by α2-agonists have also been reported [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, multiple linear regression analysis indicated a negative correlation between anterior flare reduction and combination therapy of K-115 and α2-agonists, which suggests that α2-agonists with or without K-115 possibly increase anterior inflammation in uveitis with OHT. Previous reports have proposed that adrenergic agonists decrease the volume of conjunctival cells and widen the space between cells, allowing greater access of pro-inflammatory agents and continued topical administration of α2-agonists in eyes with allergic reactions may predispose to the development of uveitis [ 24 ]. Histological findings of conjunctivitis and anterior uveitis induced by α2-agonists have also been reported [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three previous studies have investigated the role of topical pharmaceutical agents on leukocyte migration [26,31,32]. However, only one examined multiple antiglaucomatous drugs, including beta blockers, cholinergic agonists and nonselective adrenergic agonists [26].…”
Section: Discussionmentioning
confidence: 99%
“…При терапии бримонидином описано развитие гранулематозного конъюнктивита и кровоизлияний в конъюнктиву [44,50]. Фолликулярный конъюнктивит считается частой реакцией на простагландины, ингибиторы карбоангидразы, α2-адреномиметики.…”
Section: переносимость антиглаукомной терапии и побочные эффекты актиunclassified